Methods of implementation of an alpine skiing school - Ivan Bon; Mateja Očić; Igor Božić; Mislav Škovran (SportLogia, 2020)
Nowadays, various programs are used in ski schools to teach beginners. All programs have the same goal, and that is to teach beginners specific body movements with which they will be able to manage their skis. Three programs are most commonly used in alpine skiing schools. According to one program, ski beginners are taught the basics of alpine skiing exclusively with elements of parallel skiing techniques. In the second program, ski beginners acquire knowledge using elements of snowplough and parallel ski technique. The third alpine skiing learning program combines these two methods. In addition to the program, in practice there are two approaches to learning alpine skiing. The first method involves a daily trip to a ski slope or a nearby winter tourist centre, where the skiing technique is adopted and beginners return to the place of residence the same day. The second way consists of an organized, usually seven-day, winter trip, during which the basics of alpine skiing are learned every day during the stay in the ski-resort. Regardless of the learning programs used, the safety of skiers is a priority in every alpine skiing school. Therefore, it is advisable for all beginner skiers to get involved in an alpine skiing school, as this is the best way to prevent injuries.